CO2 reforming of benzene into syngas by plasma-enhanced packed-bed dielectric barrier discharge with different packing materials - Guo, Yafeng; Cheng, Shiye; Du, Yu; Lu, Na; Li, Chao; Bao, Hanchun; Zhu, Xiao; Tang, Shi-Ya (Frontiers in Chemistry, 2025)
Tar reforming has gained widely attention in the field of biomass gasification. Dielectric barrier discharge (DBD) presents a promising technology for the conversion of biomass gasification tar under ambient conditions. In this study, plasma-enhanced dual DBD (ED-DBD) combined with packing materials such as glass (SiO2) beads and SiC blocks was utilized to examine the CO2 reforming of benzene, serving as a tar analogue, into syngas. (Introduction) First, the discharge characteristics and performance metrics for benzene and CO2 conversion (Method 1) were evaluated and compared between the conventional dual dielectric barrier discharge (D-DBD) system and the ED-DBD reactor, which was augmented with SiO2 beads and SiC blocks. The findings indicated that the ED-DBD reactor incorporating SiC blocks demonstrated superior performance, achieving a benzene conversion of 51.0%, a CO2 conversion of 75.0%, and an energy efficiency for CO2 conversion of 73.9%. The results satisfy the minimum requirements for CO2 conversion and energy efficiency required for industrial application (Results and Discussion 1). Secondly, analysis via X-ray Photoelectron Spectroscopy (XPS) (Method 2) revealed that a minor proportion of carbon elements originating from the SiC blocks within the plasma region were involved in the reaction process (Results and Discussion 2). Moreover, an elevated initial concentration of CO2 in the benzene system enhanced the degradation of benzene, whereas the introduction of benzene into the CO2 system promoted the conversion of CO2. Emission spectroscopy (Method 3) corroborated the presence of active hydroxyl radical (·OH) particle during the discharge process. It suggests that the SiC-packed ED-DBD reactor more efficiently generates active OH particles during the discharge compared to the SiO2-packed ED-DBD reactor (Results and Discussion 3). This study not only offers an effective method for converting tar analogues into syngas under mild conditions but also presents an alternative approach for CO2 utilization within a carbon-neutral strategy.